1997
DOI: 10.1136/thx.52.6.528
|View full text |Cite
|
Sign up to set email alerts
|

Climate and aeroallergen levels in asthma: a 12 month prospective study

Abstract: Abstractconcentrations such as occurred in Barcelona in relation to soya bean dust have been associated Background -There is evidence to suggest that changes in weather and airborne with large numbers of acute exacerbations. 10 Inhaled pollens are an established cause of fungal spore and pollen counts may affect asthma symptoms.respiratory symptoms in humans. In New Zealand introduced species such as grasses, birch, Methods -The relationship between climate, airborne fungal spore, and pollen macrocarpa, oak, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Lewis et al [6] reported that grass pollen influenced asthma emergency visits for asthma on days of light rainfall, and no effect was detected on dry days [6]. Delfino et al [14] and Epton et al [15] did not detect associations between pollen counts and symptoms, inhaler use or peak flows. One explanation for apparent differences in pollen effects between studies may be that effect sizes are relatively small requiring a very large number of observations to obtain conventional levels of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis et al [6] reported that grass pollen influenced asthma emergency visits for asthma on days of light rainfall, and no effect was detected on dry days [6]. Delfino et al [14] and Epton et al [15] did not detect associations between pollen counts and symptoms, inhaler use or peak flows. One explanation for apparent differences in pollen effects between studies may be that effect sizes are relatively small requiring a very large number of observations to obtain conventional levels of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have detected effects of ambient fungal spores but not pollen [8, 12, 14, 15]. Additionally, reporting on only total tree or total grass pollens does not permit assessment of any relative differences in potency by group or genus within the total.…”
Section: Introductionmentioning
confidence: 99%
“…Airborne allergens, including fungal spores, and climatic changes may influence the symptoms of asthma patients. Isolated cases suggest that meteorological events such as thunderstorms and dust storms have been correlated with increased asthma-related problems in the general population (Epton et al 1997). For example, an epidemic in June 1994 occurred in London, during which the local hospitals saw a tenfold increase in hospital admissions for asthma during and immediately preceding a thunderstorm.…”
Section: Introductionmentioning
confidence: 98%
“…Since not only the spores but also the fruiting bodies of Ganoderma , Coprinus and Pleurotus contain allergens, they may induce food allergy in sensitized patients upon consumption of these mushrooms [118, 119]. Hence, basidiomycota as well as ascomycota are known to cause atopic asthma in susceptible persons [120]. The incidence of basidiomycota-caused allergy ranges from 3.5 [121] to 25.4% [122].…”
Section: Fungal Allergensmentioning
confidence: 99%